John Finney, Music Education in England, 1950-2010: the Child-Centred Progressive Tradition (2011) (Journal of the Society for Musicology in Ireland, 2013)
Review of John Finney, Music Education in England, 1950-2010: the Child-Centred Progressive Tradition (Farnham: Ashgate Press, 2011). ISBN 978-1-4094-1076-8.